Local Churches and Innovativeness: An Empirical Study of 2800 Australian Churches - Powell, Ruth (Research in the social scientific study of religion, 2018)
Changing social and cultural contexts challenge Christian churches to be innovative in their approach for ongoing sustainability and effectiveness. This paper offers an empirical study of innovation within 2,802 Australian congregations from 23 Protestant and Catholic denominations, based on the 2011 National Church Life Survey. Insights from organizational and leadership literatures were used to frame the dependent variable, ‘Innovative Church Culture’ (ICC). The independent variables were attender worship service evaluation, local church social capital, leader innovativeness and local church size. Regression analyses were based on attenders’ survey responses aggregated to the level of the local church. They were first run on the full sample, and then for each of six denominational subsamples: Anglican, Uniting, Catholic, Baptist, Lutheran and Pentecostal churches. Results found that worship service evaluation, social capital and church size explained almost half of the adjusted variance (46%) in ICC in the full sample, and ranged from 24% to 61% for the subsamples. The strongest predictor was positive experience of worship services, followed by bonding/bridging social capital. Church size and leader innovativeness were only weak positive predictors of innovative culture. Leader innovativeness was a weak positive predictor. Cultural innovativeness differed between denominations, and was highest in Pentecostal churches. The paper provides commentary on these findings and concludes with suggestions for future empirical research on the sources and outcomes of innovation.